SUCCESSION PLANNING AND SUCCESOR COMPETENCIES IN THE PORT BOARDING AND UNLOADING FAMILY BUSINESS - Wanda Gema Prasadio Akbar Hidayat; Mohammad Annas; Cynthia Sari Dewi (SEAN Institute, 2023)
This study examines succession planning and the competence of successors in the loading and unloading port family business, namely PT Samudera Krida Utama. Its original founder, who has been in charge for ten years, is still in charge of PT Samudera Krida Utama. There have been problems in the last three years. The main factor in this problem is the lack of optimal succession planning and successor competency. This research uses the perspective of Bradley and Burrough's succession planning process theory, which focuses on the factors that influence the succession planning process. This study uses qualitative research methods. Field research involved 15 informants, all family members. The results of this research show that the succession planning and competency of successors that are currently running are not optimal, and the succession planning and competency of successors that should be owned and implemented prepare succession planning and competency. This study also presents new theoretical findings, namely that the basic competencies that a successor must have are communication quality, expertise in finance, marketing, technical skills, decision-making ability, level of education, and interpersonal skills. This result was found by elaborating on the theories of Bradley, Burrough, and Fishman. Next, PT Samudera Krida Utama must concentrate on capabilities, experience outside the company, experience inside the company, and level of education when implementing succession planning. This finding combines with two theories by Bradley, Burrough, and Chrisman et al. If this is done jointly and optimally, the succession planning and competency of PT Samudera Krida Utama's successors will run smoothly, and the company will continue to develop.